Prevalence and Distribution of Musculoskeletal Disorders among Dental Students in AIMST University: A Cross-Sectional Study - Ajimol Theresa Jose; Chang Choy Kim; Emily Su Yen Ee; Lee Qi Hui; Mok Hui Ting; Moy Ai Leng (Oral Sphere Journal of Dental and Health Sciences, 2026)
Introduction: Musculoskeletal Disorders (MSDs) pose a serious global concern for dental students. Most MSDs arise from repetitive motions, poor posture, and prolonged static postures, all of which are typical of dental education. Clinical procedures, such as restorative, endodontic and periodontal treatment procedures, increase the likelihood of MSDs to develop in students' neck, upper thoracic region, low back, and wrists. Methods: The data for this cross-sectional study was collected from undergraduate dental students at AIMST University to determine how prevalent MSDs are among that group. Specifically, the survey used a standardized questionnaire to obtain information about the degree of musculoskeletal discomfort in the neck, upper back, lower back, wrists, and fingers of each student. It also sought to identify what students do to relieve their pain. Results: A total of 112 participants participated in the research, which showed a significant number of BDS Year 5 students reported the greatest prevalence of MSDs (with an emphasis on the upper back and lower back areas). Endodontic and restorative procedures accounted for the majority of pain experienced by the students, whereas physiotherapy and massage represented the most common strategies employed to alleviate pain. The data collected from this study revealed that the students generally have limited knowledge of ergonomics and therefore require education about maintaining proper posture and using proper ergonomic techniques. Conclusion: MSDs are highly prevalent among dental students, with BDS Year 5 students being the most affected. Interventions such as ergonomic education, workstation improvements, and physical activity promotion are essential to reduce MSD risks. Early prevention strategies could enhance students' well-being and academic success, minimizing long-term impacts on their careers.